A wonderlandiful world - Hale, Shannon (New York : Little, Brown and Company, 2014)
After a mysterious being from Wonderland infects Ever After High with a strange magic, everything goes topsy-turvy. The students transform into animals and objects, palace mice talk, and the beautiful green grounds on campus fade to black-and-white. It's a curse that threatens to give the school - and the students' lives - a very unhappy ending.
Keywords: Boarding schools -- Juvenile fiction; Fairy tales